Antidepressant-like and anti-oxidative efficacy of Campsis grandiflora flower. (26th September 2015) - Yu, Hai-Chuan; Wu, Jiao; Zhang, Hong-Xing; Zhang, Hai-San; Qiao, Ting-Ting; Zhang, Ji-Xia; Zhang, Gao-Li; Sui, Juan; Li, Li-Wei; Zhang, Li-Rong; Lv, Lu-Xian
Abstract: Objectives: Our study aimed to investigate the antidepressant-like effect of ethyl acetate extract of the flowers of Campsis grandiflora (EFCG) in a mice model of chronic unpredictable mild stress (CUMS). Methods: HPLC-Q-TOF-MS was used to identify the chemical constituents of EFCG. The DPPH assay and ABTS radical-scavenging assay were performed to measure the antioxidant properties. The protective properties of EFCG against H2 O2 -induced oxidative damage were analysed in PC12 cells. The changes of behaviour profiles were investigated by using open-field test, sucrose preference test, forced swimming test (FST) and tail suspension test (TST). Brain tissue samples of mice were collected, and antioxidative measure levels were measured. Key findings: The result showed that EFCG had the most active anti-oxidative effect and the protective effect against H2 O2 oxidative injury in PC12 cells. Treatment with the EFCG significantly reduced the depressant-like severity and immobility period as compared with untreated CUMS mice in FST and TST. Moreover, EFCG significantly elevated the contents of superoxide dismutase, Glutathione Peroxidase and decreased the contents of Malonaldehyde (MDA) in mice brain. Conclusions: Our study found first the antidepressant activity of the EFCG. The results suggested the therapeutic potential of EFCG for depressive disorder.